2018
DOI: 10.1101/324277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BiFET: A Bias-free Transcription Factor Footprint Enrichment Test

Abstract: Transcription factor (TF) footprinting uncovers putative protein-DNA binding via combined analyses of chromatin accessibility patterns and their underlying TF sequence motifs. TF footprints are frequently used to identify TFs that regulate activities of cell/condition-specific genomic regions (target loci) in comparison to control regions (background loci) using standard enrichment tests. However, there is a strong association between the chromatin accessibility level and the GC content of a locus and the numb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…To this end, we used the maelstrom tool (Bruse & van Heeringen, 2018) to perform a differential motif enrichment analysis revealing which known TF motifs are specifically enriched in cell type-specific accessible regions. In parallel, the BiFET tool (Youn et al, 2019) was employed to identify TF footprints (FP: less accessible regions within highly accessible regions where a TF motif is found) (Li et al, 2009) enriched in the DARs found in each differential accessibility contrast (). The results of the maelstrom and of the BiFET analyses were integrated by selecting the TF motifs whose differential enrichment trend correlates with the corresponding FP enrichment profile and with the TF expression during the differentiation.…”
Section: Prediction Of Stage-specific Transcription Factor Activity P...mentioning
confidence: 99%
“…To this end, we used the maelstrom tool (Bruse & van Heeringen, 2018) to perform a differential motif enrichment analysis revealing which known TF motifs are specifically enriched in cell type-specific accessible regions. In parallel, the BiFET tool (Youn et al, 2019) was employed to identify TF footprints (FP: less accessible regions within highly accessible regions where a TF motif is found) (Li et al, 2009) enriched in the DARs found in each differential accessibility contrast (). The results of the maelstrom and of the BiFET analyses were integrated by selecting the TF motifs whose differential enrichment trend correlates with the corresponding FP enrichment profile and with the TF expression during the differentiation.…”
Section: Prediction Of Stage-specific Transcription Factor Activity P...mentioning
confidence: 99%
“…Several tools have been developed to detect footprinting from ATAC-seq data, which are based on multi-omics data and hidden Markov algorithm [1, 10]. ATAC-seq footprinting has been applied to TF network prediction [11], comparison of TF activity [10], and identifying TFs enriched in PBMC-specific peaks [12].…”
Section: Introductionmentioning
confidence: 99%